Time-Dependent Diffusion Coefficient of Fe in MgB2 Superconductors - Ülgen, Asaf Tolga; Belenli, İbrahim (JOURNAL OF SUPERCONDUCTIVITY AND NOVEL MAGNETISM, 2017)
The iron (Fe) diffusion in superconducting MgB2 bulk samples has been studied for sintering time durations of 15 min, 30 min, 1 h, 2 h, and 4 h at 900(ay)C. Fe coating bulk polycrstalline superconducting MgB2 samples for Fe coating were prepared by pelletizing and used in the diffusion experiments with initial sintering at 800(ay)C for 1 h. A thin layer of Fe was coated on MgB2 pellets by evaporation in vacuum. Effects of Fe diffusion on the structural, electrical, and superconducting properties of MgB2 have been investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), infrared spectroscopy (IR), energy-dispersive X-ray spectroscopy (EDS), and resistivity measurements. Fe diffused samples have slightly increased critical transition temperatures and have larger lattice parameter c values, in comparison with bare samples. Fe diffusion coefficients were calculated from depth profiles of c parameter and room temperature resistivity values. Depth profiles were obtained by successive removal of thin layers from Fe diffused surfaces of the samples. Our results have shown that the Fe diffusion coefficient decreases with increasing sintering time and resistivity measurements can be utilized for determination of diffusion coefficient.
Keywords: Superconducting materials; Magnesium diboride; Fe-diffusion and diffusion coefficient